Analisis Manajemen Pengendalian Mutu Produksi pada Bakpiapia Djogja Tahun 2016 Berdasar Perencanaan Standar Produksi - Mardiyah Rusydah; Yuana Tri Utomo (At-Tauzi : Jurnal Ekonomi Islam, 2019)
This study aims to analyze the quality control of production in bakpiapia based on production standard planning. This research is descriptive qualitative. Data collection methods using interviews, documentation and observation. Data analysis techniques using the interactive model of Milles and Huberman. The results showed that production quality control in bakpiapia based on standard production planning has been categorized as effective and efficient because bakpiapia already has measurements related to quality standards of quality and halal raw materials, trained labor, adequate equipment, regular production processes and excellence in product innovation. Based on the results of this study, it is recommended to the bakpiapia Yogyakarta to always improve the quality of production, which is to prioritize halal raw materials and more hygienic production processes.